External Validation of the WORSEN Score for Prediction the Deterioration of Acute Ischemic Stroke in a Chinese Population - Xu, Yicheng; Chen, Yu; Chen, Ruiwei; Zhao, Fei; Wang, Peifu; Yu, Shengyuan (Frontiers in Neurology, 2020)
Background: Early neurological deterioration (END) has been recognized as a serious neurological complication after acute ischemic stroke. However, to date, the WORSEN score was the only one scoring system specifically developed to detect END events in acute ischemic stroke patients. The purpose of this study was to investigate the WORSEN score’s utility in China, and to determine the potential predictors of END in acute stroke patients. Methods: Consecutive patients with acute ischemic stroke admitted to the Department of Neurology, Aerospace Center Hospital between March 2015 to February 2017 were recruited into the study’s cohort and divided into two groups: patients with and without END . END was defined as either an increase in two or more NIHSS points , an increment of at least one point in motor power or a description of fluctuating of clinical symptoms in medical reports during the first 7 days after admission. Severe END was defined as an increase of NIHSS ≥ 4 points from baseline during the first 7 days after admission. Results: 354 patients with acute ischemic stroke were enrolled in the present study and 67.5% were male. END occurred in 90 of these patients and severe END occurred in 55 of these patients. Logistic regression analysis showed that an initial NIHSS score ≥8, diameter of infarction , striatocapsular infarction, and TOAST type of large arterial atherosclerosis were independent predictors for END. The area under the ROC curve (AUC) of the WORSEN score for the prediction of END was 0.80 (95%CI 0.75-0.84), with a sensitivity of 62.22%, a specificity of 88.26%, positive predictive values of 64.37% and negative predictive values of 87.27%. Meanwhile, the AUC of the WORSEN score for the prediction of severe END was 0.82 (95%CI 0.78-0.86), with a sensitivity of 70.91%, specificity of 83.95%, positive predictive values of 44.83% and negative predictive values of 94.01%. Conclusion: END is a relatively common neurological complication in patients with acute ischemic stroke. Our findings showed that the WORSEN score had a good predictive value for identifying patients with END in a Chinese population. Moving forward, multi-center studies are required for further validations.